2007
DOI: 10.1136/jnnp.2006.108753
|View full text |Cite
|
Sign up to set email alerts
|

How generalised are secondarily "generalised" tonic clonic seizures?

Abstract: In clinical practice, epileptic seizures with focal onset and subsequent generalised motor involvement are referred to as secondarily generalised seizures. The purpose of this study was to investigate the degree of electrophysiological generalisation in seizures that are clinically secondarily generalised. Intracranial EEG recordings of secondarily generalised tonicclonic seizures were visually and quantitatively analysed for the presence of epileptiform activity. In 24 (26%) of 93 seizures recorded from 17 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 6 publications
1
41
0
Order By: Relevance
“…This might help to refine already existing approaches in order to increase predictive performance, to develop new analysis concepts and measures, and to guide basic science investigations to specific mechanisms. Of equal importance is to improve the understanding of mechanisms underlying seizure termination, which, in turn, might provide valuable information about seizure-initiating mechanisms [9,10,[144][145][146][147][148] and might guide new developments for seizure control [149]. Since such studies might require access to deep brain structures and other locations in the epileptic network that cannot be explored in human studies, due to safety concerns, there is a strong need to improve existing and develop new spontaneously seizing animal models of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…This might help to refine already existing approaches in order to increase predictive performance, to develop new analysis concepts and measures, and to guide basic science investigations to specific mechanisms. Of equal importance is to improve the understanding of mechanisms underlying seizure termination, which, in turn, might provide valuable information about seizure-initiating mechanisms [9,10,[144][145][146][147][148] and might guide new developments for seizure control [149]. Since such studies might require access to deep brain structures and other locations in the epileptic network that cannot be explored in human studies, due to safety concerns, there is a strong need to improve existing and develop new spontaneously seizing animal models of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Focal seizures with secondary generalization may show some EEG asymmetry even during the generalized phase 86, 87 . Intracranial EEG has demonstrated that generalized tonic-clonic seizures are not truly generalized, but may spare some brain regions 88 .…”
Section: Generalized Tonic-clonic Seizuresmentioning
confidence: 99%
“…There is some debate as to whether these seizures are truly generalized in the sense of homogeneous brain involvement or whether involvement is biased towards corticothalamic networks (Meeren et al, 2005; Schindler et al, 2007). This distinction is important as it can help to identify and separate brain structures involved in IoC.…”
Section: The Consciousness Systemmentioning
confidence: 99%